World of consumption - Fine, Ben (London, 1993)
In the opinion of many people the last decade saw the arrival of the `consumer society'. However, the response of social theory to consumerism has been barely appropriate to the scale of the changes. As an antidote to this, the authors propose the adoption of a new, more inclusive theoretical approach, based on "systems of provision". This emphasises different forms of determination for different products. It also emphasises the essential continuity between the various aspects of consumption: production, distribution, marketing, advertising and sales.
Keywords: Consumption